Electroconvulsive therapy in Parkinson´s disease - Humberto Calderón-Fajardo; Amin Cervantes-Arriaga; Rodrigo Llorens-Arenas; Jesús Ramírez-Bermudez; Ángel Ruiz-Chow; Mayela Rodríguez-Violante (Arquivos de Neuro-Psiquiatria)
Purpose To analyze the effectiveness of electroconvulsive therapy for the management of depression and/or psychosis refractory to drug therapy in patients with Parkinson disease.Methods A retrospective study was carried out including patients treated with electroconvulsive therapy during the period between 2002 and 2013. A review of the literature was performed.Results A total of 27 patients were included. In regards to the neuropsychiatric diagnosis, 14 patients had major depression, 12 patients had both psychosis and depression, and only one patient had isolated psychosis. The mean number of electroconvulsive therapy sessions was 12 ± 2.8. After electroconvulsive therapy, all patients showed a statistically significant improvement in the Brief Psychiatric Rating scale (reduction of 52% points) and Hamilton Depression Rating Scale (reduction of 50% points) independent of the presence of psychosis, depression or both.Conclusion Electroconvulsive therapy is effective for the treatment of refractory neuropsychiatric symptoms in Parkinson’s disease.